2013
DOI: 10.1002/celc.201300063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Scale Imaging of Water Near Charged Surfaces

Abstract: The orientation of water molecules on water bilayers is investigated on Cu(111) by a combination of scanning tunneling microscopy and density functional theory. Theory predicts that the application of a field reorients the adsorbed water molecules at a distance of close to a nanometer from the surface. Experimental evidence is presented for this prediction. Furthermore, the process differs strongly between adsorption on two and on three ordered layers. We propose that these results give insight into the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In the search for greater understanding of ice nucleation processes, we are faced with an unassailable challenge: that the surface sites within which nucleation occurs are only a few nanometers in size. This is much too small to observe the process directly with any presently known experimental techniques, although microscopists continue to make strides in the molecular imaging of ice and of transient phenomena, which may one day lead us to that goal ( 38 , 39 ). However, for now, we are forced to glean knowledge of the mechanism of nucleation indirectly, through the study of the crystals which result from it.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for greater understanding of ice nucleation processes, we are faced with an unassailable challenge: that the surface sites within which nucleation occurs are only a few nanometers in size. This is much too small to observe the process directly with any presently known experimental techniques, although microscopists continue to make strides in the molecular imaging of ice and of transient phenomena, which may one day lead us to that goal ( 38 , 39 ). However, for now, we are forced to glean knowledge of the mechanism of nucleation indirectly, through the study of the crystals which result from it.…”
Section: Discussionmentioning
confidence: 99%
“…Another prime candidate for application of this model is two-dimensional ice. It was possible to grow an ice mono-layer 44 to a bi-layer and a multi-layer 45 on a Ru or a Cu surface. Theoretically, the bi-layer ice was previously simulated with molecular dynamics within confinement.…”
Section: Discussionmentioning
confidence: 99%
“…Water in the vicinity of hydrophobic and hydrophilic sites of the protein exhibits a dynamical behavior which is quite distinct when compared to bulk water. [20][21][22][23][24][25][26][27] Recently, experiments and simulations with water at the GFP and CYP proteins showed that water molecules at the biomolecule surface present a very slow dynamics and they get stuck in some places, suggesting the presence of fractal traps on the protein surface. 28,29 In these systems, the water near the protein exhibits a subdiffusive behavior in which the mean squared displacement (MSD) of the molecules grows nonlinearly with time, i.e., ⟨r 2 (t)⟩∝ t µ , in which µ < 1 for subdiffusion.…”
Section: Introductionmentioning
confidence: 99%